Measure up : A Better Way to Calculate GDP - Alexander, Thomas (Staff Discussion Notes; Staff Discussion Notes ;, 2017)
To derive real GDP, the System of National Accounts 2008 (2008 SNA) recommends a technique called double deflation. Some countries use single deflation techniques, which fail to capture important relative price changes and introduce estimation errors in official GDP growth. We simulate the effects of single deflation to the GDP data of eight countries that use double deflation. We find that errors due to single deflation can be significant, but their magnitude and direction are not systematic over time and across countries. We conclude that countries still using single deflation should move to double deflation.